Exercises in critical reading a seminar - Lacson, Milagros (Zantua) 1930- ([Quezon City s.n.], 1964)
The exercises suggested in this paper include the following skills: sensing the main idea, noting significant details, determining relevant ideas, reading between the lines, forming opinions, making reasoned conclusions, sensing agreement or disagreement among authors, sensing a writer's bias, judging the validity of an author's premise, distinguishing between fact and opinion, sensing connotations, and judging the appropriateness of an author's language.
Thesis (M.A.T.)--University of the Philippines
Keywords: Reading